Fostering Excellence: Enhancing Insights and Competencies in Business Education - Adininggar, Dika Ayu; Hanis Bachrodin; Ludi Wishnu Wardana; F Danardana Murwani; Andy Prasetyo Wati (Social Science Studies, 2024)
Research Aims: This research aims to explore and improve understanding and competence in business education. With a focus on developing curricula that are relevant to industry needs and technological developments, this research will identify best practices in business teaching and learning. Design/methodology/approach: This research uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that with rapid changes in technology, global markets, and industrial dynamics, business education must continue to adapt so that students can face complex challenges and opportunities in the future. Research Findings: This research provides an opportunity to identify best practices, integrate the latest industry insights into the curriculum, and improve the effectiveness of teaching and learning methods. Theoretical Contribution/Originality: Thus, it is hoped that the research results can make a significant contribution to strengthening the existence of business education as a support for developing competent and adaptive human resources in a dynamic global context.